Role of ascitic fluid study in early detection of spontaneous bacterial peritonitis in asymptomatic patients of cirrhosis of liver - Kabir, Md Asadul; Sarkar, Md Maniruzzaman; Bodruddoza, Kazi; Bari, Anwarul; Chowdhury, Jewel (Bangladesh Journal of Medicine, 2019)
Spontaneous bacterial peritonitis (SBP)is an acute bacterial infection of ascitic fluid and one of the commonest complication of patients with cirrhosis presented with ascitis. Routine analysis of ascetic fluid particularly for polymorphonuclear leukocyte is an important tool for detecting spontaneous bacterial peritonitis including clinically unsuspected and asymptomatic patients also. Thus it helps in reducing mortality and morbidity by early and effective detection of spontaneous bacterial peritonitis. Objective: This study was carried out to evaluate the role of ascitic fluid analysis in early detection of spontaneous bacterial peritonitis and to document the proportion of spontaneous bacterial peritonitis present asymptomatically. Study design: This was a cross sectional observational study prospective in nature on 50 cases of diagnosed chronic liver disease patients in indoor of department of medicine of Sir Salimullah medical college Hospital, Dhaka from 02/01/13 to 01/07/13, for a period of 6 months. Result: The study showed that age frequency 5(10%) were from 21-30 years, 15(30%) were from 31- 40 years, 15(30%) were from 40 -50years and 15(30%) were from >50 years of age. Out of 50 patients, 38(76%) were male and 12(24%) were female patients. The etiology of liver cirrhosis was hepatitis B virus in 22(44%), hepatitis C virus in 4(8%), alcohol in 1 (2%) and others in 23(46%) patients. Among 50 patients, 16(32%) were spontaneous bacterial peritonitis and 34(68%) were non spontaneous bacterial peritonitis. The symptoms of spontaneous bacterial peritonitis were upper GI bleeding in 8 patients (50%), fever in 12 patients (75%), abdominal pain in 10 patients (62.5%), abdominal tenderness in 7 patients (43.75%), hepatic encephalopathy in 9 patients (56.25%), jaundice in 10 patients (62.50%), splenomegaly in 16 patients (100%), ascites in 16 patients (100%) and 5 (10%) patients were asymptomatic spontaneous bacterial peritonitis. According to Child Pugh’s, 2(12.5%) patients were at stage-A, 5 (31.25%) patients were at stage-B and 9 (56.25%) patients were at stage- C. Ascitic fluid characteristics (mean +SD) of all patients were, Total cell counts/mm3 (571+499.9), Neutrophil counts/mm3 (144.8+445.1), Sugar (112+38.19) mg/dl, Protein (1.85+1.09). Among SBP patients, 7 (43.75%) have PMN cell counts 250-750/mm3, 6 (37.50%) have 750-1750/mm3 and 3 (18.75%) have >1750/mm3. Conclusion: Spontaneous bacterial peritonitis is a common complication of decompensated cirrhotic patients. The classical signs of SBP (e.g. abdominal tenderness or fever) may not be present. We observed the trend towards more frequent occurrence of the infection in patients suffered from severe liver disease (e.g. Child Pugh’s –C) and the role of ascitic fluid analysis is statically significant. Bangladesh J Medicine Jan 2019; 30(1) : 9-18